Effect of polymerised type I collagen on hyperinflammation of adult outpatients with symptomatic COVID‐19 - Méndez‐Flores, Silvia; Priego‐Ranero, Ángel; Azamar‐Llamas, Daniel; Olvera‐Prado, Héctor; Rivas‐Redonda, Kenia Ilian; Ochoa‐Hein, Eric; Rojas‐Castañeda, Estefano; Urbina‐Terán, Said; Septién‐Stute, Luis; Hernández‐Gilsoul, Thierry; Aguilar‐Morgan, Adrián Andrés; Fernández‐Camargo, Dheni A.; et al. (My University, 2022)
Dear Editor: Although dexamethasone is approved for the hyperinflammation treatment of hospitalised COVID-19 patients, non-hospitalised patients do not benefit from this therapy.1 A potential drug for treating COVID-19 patients is polymerised type I collagen (PTIC). A downregulator of pro-inflammatory cytokines, adhesion molecules (ELAM-1, VCAM-1, and ICAM-1), cyclooxygenase (Cox)-1 enzyme and the collagenases expression through the modulation of transcription of factor NF-kB.2-6 The intramuscular or subcutaneous administration of PTIC to patients with active RA (Phase II studies) improved the count of swollen joints and morning stiffness; 57% of patients achieved an ACR score of 50, and 30% had disease remission with this therapeutic combination. PTIC was safe and well-tolerated in long-term treatment, without adverse effects. © Clinical and Translational Medicine